The functional assessment of autotransplanted splenic tissue by its capacity to remove oxidatively modified erythrocytes - YALÇIN, AHMET SUHA; HAKLAR, GONCAGÜL (My University, 1997)
Free radicals and reactive oxygen species have been implicated in the pathogenesis of a variety of hematologic diseases and erythrocyte aging. Aged erythrocytes are removed from the circulation primarily by the spleen. In this study, we aimed to determine the functional effectiveness of autotransplanted splenic tissue by its capacity to remove oxidatively modified erythrocytes from the circulation. Our experimental model in rats includes splenectomy with autotransplantation of 80% of the excised splenic tissue into the omental pouch. In this model, free radical damage was estimated by different parameters of lipid peroxidation such as carbonyl content and thiobarbituric acid reactive substances (TBARS), together with Heinz body formation. Our results have shown that splenic autotransplantation was effective in removing oxidatively modified, aged erythrocytes from the circulation.
Keywords: Animals; Male; Rats; Rats, Wistar; Lipid Peroxidation; Transplantation, Autologous; Half-Life; Regeneration; Free Radicals; Erythrocyte Aging; Spleen